Using web browsing histories to facilitate multi-method research - Menchen-Trevino, Ericka (AoIR Selected Papers of Internet Research, 2016)
If someone has any relationship at all to their web browsing history, it is probably best summarized in one word, “delete.” Despite the sensitive nature of this data, if given the ability to explore and better understand their own data and remove what they choose, some web users may opt-in to sharing this data with researchers they trust. In fact, the informed consent process could demystify this often poorly understood source of information and give individuals better tools for understanding and controlling their own browsing data logs. Furthermore, this user-focused data crosses between platforms where data is often siloed, such as different social media sites and web services making it particularly useful for extending the insights of platform-based studies of digital traces. The Herodotus (name changed for anonymous review) project has developed an open-source web browser extension with the goal of informing users of the insights available in their browsing history data through visualizations and analytics. The extension allows users to opt-in to share their data with a research project after viewing interactive visualizations of the browsing data that already exists on their browser. Participants are directed to an online survey which allows for the collection of both observed and self-reported information about web browsing. This can help researchers assess the accuracy of self-reports, but perhaps more importantly it can address questions about the impact (or lack thereof) of attitudes on behaviors in a more valid way than self-reported behavior data can provide.